2019
DOI: 10.17576/jkmjc-2019-3501-13
|View full text |Cite
|
Sign up to set email alerts
|

Dancing with the Impropriety of Media: How Indonesian Consumers Think and Behave towards the Unethical and Illogical Online News

Abstract: The rise of online media makes us now everyday are bombarded by a number of online news content which are sometimes unethical and illogical. Without considering the adverse effects it causes, the media continue to treat news consumers with inappropriate content. News consumers as if hypnotized to 'dance' following the rhythm of that impropriety. How do news consumers, especially in Indonesia, think and behave towards the issue? This paper captures the voices of consumers and reviews their judgements regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…When the audiences have a free choice, they also would create their news agenda different from the status quo -setting what stories they want to appear as news, and dictating the contents of the news presented to them (Stray, 2018). If the news is a collective product of the system, then the behaviour of news is a reflection of collective and/or institutional behaviour (Wijaya, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…When the audiences have a free choice, they also would create their news agenda different from the status quo -setting what stories they want to appear as news, and dictating the contents of the news presented to them (Stray, 2018). If the news is a collective product of the system, then the behaviour of news is a reflection of collective and/or institutional behaviour (Wijaya, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, many surveys concluded that television remains the main source of information for most of the Indonesian population (Indotelko, 2018;Lembaga Survei Kedai Kopi, 2018). It has also been argued that mainstream online media in Indonesia are subjected to the media logic that prioritise the most effective metrics such as traffic, clicks and pageviews which promotes manipulative practices such as click baiting and sensationalism (Wijaya, 2019). The problem is then, of course, the extent to which the media organisation considers how social media is part of their future strategy to reach a new, younger audience, who are very close to technological innovations, have many options related to their media consumption, and are also more selective in looking for information.…”
Section: Resultsmentioning
confidence: 99%
“…Although online media is currently overgrowing and becoming a channel for many brands in stimulating purchases (Westergaard, 2018) and attracting millenials (Hall, Towers & Shaw, 2017) as well as online market places continue racing (Basul, 2019), the offline store and retail still have an allure. In addition to much inappropriate online media regarding their reputation and behaviour (Wijaya, 2019) so it is risky for brand communication, offline or physical shopping is considerably more 'comfortable' and 'safe' related to sensorial experiences, interpersonal communication, and after-sales service (Vroom, 2016). Wei-yu and Zhen in Yu, Sun, and Guo (2019) suggest some concerns regarding consumer preferences for in-store channels, including price, quality, comfort, accessibility, services provided, and product variations, while Boardman and Mccormick (2018) suggest convenience and enjoyment as consumer preferences for physical store channel, and convenience, selection, adventure/ exploration and idea shopping for the ecommerce shopping channel.…”
Section: Introductionmentioning
confidence: 99%